An Understanding of the Islamic Banking Industry from Customers’ Perspective - Chowdhury, Rebeka Sultana (Asian Business Review, 2016)
During the last decade, conventional banks faced stiff competition from Islamic bank. The main purpose of the study is to find out the customers’ perspective on Islamic banking in Bangladesh. The study was based on both primary and secondary data. For collecting primary data, a questionnaire survey was conducted among Islamic banks’ customers. Selection of respondents was based on random sampling as well as the convenient sampling method. Customer opinions were measured by a 5-point Likert scale. Customers’ perspectives have been measured with respect to various aspects (service quality, profit rate, service charge, internet banking, employee proficiency, etc.). Findings of the study reveal that the respondents think positively about almost all aspects of the Islamic bank. JEL Classification Code: G21